2011
DOI: 10.1038/onc.2011.244
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of CD146 as an ERM-binding protein offers novel mechanisms for melanoma cell migration

Abstract: Tumor cell migration is a well-orchestrated multistep process that drives cancer development and metastasis. Previous data indicated that CD146 expression correlates with malignant progression and metastatic potential of human melanoma cells. However, the exact molecular mechanism of how CD146 promotes melanoma cell migration still remains poorly understood. Here, we report that CD146 physically interacts with actin-linking ezrin-radixin-moesin (ERM) proteins and recruits ERM proteins to cell protrusions, prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
85
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 54 publications
6
85
1
1
Order By: Relevance
“…20,21,32 In agreement with these findings, we demonstrate that MCAM expression also affects the migration of hMSC ( Figure 1H). Luo et al suggested a possible molecular mechanism whereby MCAM may be involved in cytoskeleton remodeling and cell migration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…20,21,32 In agreement with these findings, we demonstrate that MCAM expression also affects the migration of hMSC ( Figure 1H). Luo et al suggested a possible molecular mechanism whereby MCAM may be involved in cytoskeleton remodeling and cell migration.…”
Section: Discussionsupporting
confidence: 89%
“…These authors demonstrated an association between MCAM and ERM proteins that further induced RhoA activation. 21 Other groups showed that inhibition of RhoA induces cell migration. 33 We found elevated RhoA activity in hMSC upon MCAM knockdown with induced stress fiber formation and reduced migration (Online Supplementary Figure S4).…”
Section: Discussionmentioning
confidence: 99%
“…2e). We have previously reported that CD146 promotes melanoma cell migration by activating small GTPase RhoA 18 . RhoA is an important component of the non-canonical Wnt pathway located downstream of Dvls.…”
mentioning
confidence: 99%
“…Later on, CD146 was also identified as a factor in angiogenesis, and tumour cell invasion and migration [14][15][16][17] . We have previously reported that CD146 regulates cell migration through cytoskeleton proteins by activating the small GTPase RhoA 18 . However, the underlying mechanism of CD146 has remained elusive.…”
mentioning
confidence: 99%
See 1 more Smart Citation